Carreira outsider: um estudo sobre o processo de rotulação da carreira de músico em Minas Gerais, Brasil. 2018 - Barros, Leandro Eduardo Vieira (2018)
The study of careers became an interest topic in different areas of knowledge (Administration, Psychology and Sociology); however, researches often focus on professional career models and the dichotomy between individual and organization. Such studies thus leave a gap regarding the subjective view of career and social interaction of the individual in the development of his/her profession. In this context, the general objective of this thesis is to identify how the labeling process of the outsider career for musicians occurs and what are the social and professional implications of having an outsider career in the municipalities of São João del Rei and Tiradentes. Regarding the epistemological positioning, the research based on the interpretative perspective with sociological thinking on the symbolic interactionism. The approach was qualitative, with the following techniques of data collection: observation, interview with semi-structured script and projective technique. The subjects were defined by accessibility and the number of responses by saturation. For the analysis of the data, thematic analysis was used. From the results, it is demonstrated that the first contact of the individual with music was during the primary socialization, that is, in the family, or in the second socialization, that is, friends and church. After the contact with music, the first opportunities to do remunerated shows began to appear. The musicians who did not have this opportunity presented themselves free of charge to become known in the region, emphasizing that most are self-taught. After this initial insertion, the musician initiates the investment in the career, through network page, clip, video and instruments. All of them report that they have a dream of being recognized nationally but affirm that career success is directly associated with financial investment. In addition, they emphasize that there are many musicians that has been d oing success, but they do not possess a musical talent. This is because the musician, when making use of technology, can tune the voice. The technology is also used in the process of spreading the career. It is evidenced the difficulty in the management of the career, particularly in the process of selling the shows. Faced with career difficulties, some have thought about leaving the profession, but on the other hand, they like the autonomy they have to organize their work schedule. In the context of social interaction, the OMB (Brazilian Order of Musicians) has an incipient role in defending the interests of the musician's career, and there is a strong competition in the market, which reduces the amount of the musician's cache; in this way, they are autonomous and experience financial difficulties. The market influences the musical style; thus, it may be noted that not all musicians started playing or like the country genre. The hiring process is informal and the indication for show remains in a meaningful way. The musicians like the interaction with the audience and consider that their goal is to provide happiness to the audience. Some musicians face pressures from family and partners to leave the career. Age and beauty are considered important career factors. Working hours are irregular, with performance of more than one show per day. Due to its specificities, the career is related to negative characteristics of the society, which evidences the labeling process. It has been concluded that the career of musician is considered outsider by the society, friends and relatives due its professional practice characteristics. Finally, the main limitation is that the method used does not allow generalizations although it was efficient to respond to the proposed objectives. For further research it is suggested to study the objective and subjective dimension of the career and their interaction with the social actors involved